2017
DOI: 10.1016/j.ejso.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after near-infrared fluorescence-guided resection of colorectal liver metastases: A retrospective multicenter analysis

Abstract: BACKGROUND Several studies demonstrated that intraoperative near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG) identifies (sub)capsular colorectal liver metastases (CRLM) missed by other techniques. It is unclear if this results in any survival benefit. This study evaluates long-term follow-up after NIRF-guided resection of CRLM using ICG. METHODS First, patients undergoing resection of CRLM with or without NIRF imaging were analyzed retrospectively. Perioperative details, liver-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 28 publications
(31 reference statements)
3
70
0
1
Order By: Relevance
“…Furthermore, ICG accumulates into well‐differentiated hepatocellular carcinoma (HCC), resulting in complete fluorescence signal rather than a dark center. In a retrospective cohort study in our institute it was shown that NIR fluorescence imaging of colorectal liver metastases was able to identify more and smaller tumors, resulting in reduced recurrences in a subset of patients . Twenty‐one studies evaluated the use of NIR fluorescence imaging with ICG for liver tumor detection, both primary tumors as metastatic spread of colorectal, uveal, breast, and pancreatic cancer …”
Section: Tumor Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ICG accumulates into well‐differentiated hepatocellular carcinoma (HCC), resulting in complete fluorescence signal rather than a dark center. In a retrospective cohort study in our institute it was shown that NIR fluorescence imaging of colorectal liver metastases was able to identify more and smaller tumors, resulting in reduced recurrences in a subset of patients . Twenty‐one studies evaluated the use of NIR fluorescence imaging with ICG for liver tumor detection, both primary tumors as metastatic spread of colorectal, uveal, breast, and pancreatic cancer …”
Section: Tumor Imagingmentioning
confidence: 99%
“…Dashed arrow: a preoperative suspected lesion could be recognised by its characterizing fluorescent rim. Reprinted by permission from Elsevier: European Journal of Surgical Oncology © 2017…”
Section: Tumor Imagingmentioning
confidence: 99%
“…Since the initial reports in 2009, more than 700 hepatectomy cases with the use of intraoperative fluorescence imaging for identification of liver tumors have been reported, with fairly high sensitivity (70% to 100% on liver surfaces or resected specimens; Table ) . For further clinical applications of the present technique, we need to establish a protocol of ICG administration and fluorescence imaging, although it seems to be difficult to optimize the dose and timing of ICG injection for liver tumor imaging in the centers where ICG should also be administered for preoperative liver function estimation.…”
Section: Clinical Applications Of Fluorescence Imaging For Liver Tumorsmentioning
confidence: 99%
“…Time Region Case Male Lap Surgical Mean size(cm) Kaibori [11] 2011 Japan 52/50 76/26 0/0 5.3/5.0 Handgraaf [12] 2017 Netherlands 67/87 38/56 0/0 7.4/3.2 Nishino [6] 2017 Japan 23/29 19/17 0/0 -Aoki [13] 2018 Japan 25/72 15/44 25/72 2.9/2.22 Chen [14] 2019 China 12/12 9/10 12/12 5.03/4.62 Zhou [15] 2019 China 21/21 15/15 21/21 3.1/3.2 Zhang [16] 2019 China 13/11 8/9 13/11 -Yao [17] 2019 China 28/27 23/22 0/0 6/8 Xiao [18] 2019 Six studies reported perioperative bleeding, and three of the studies did not provide specific data, so the final study included seven studies and 516 patients. There was significant heterogeneity between the groups (I 2 =88%), so a random effects model was used.…”
Section: Authormentioning
confidence: 99%